RUSSİAN ORTHODOX CHURCH, AN INSTRUMENT İN RUSSİAN FOREİGN POLİCY? - Берктай, Деніз; Berktay, Deniz (Київський національний університет імені Т. Шевченка, 2024)
This article tries to analyze the cooperation between the Russian state and the Russian Orthodox Church (ROC) from the past to the present. As it will be described below,in Russia, the state has almost everytime had domination over the church. Besides, the Russian Orthodox Church, throughout the history, formed the ideological pillars of Russia’s foreign policy, such as, Russian messianism. The church began to be used as a soft power of Moscow especially during the Second World War. Since then, the ROC has played a role of soft power in the foreign policy of the state. Since then, the US has been in cooperation with the Constantinople Patriarchate, while the Kremlin has backed the ROC. After the Soviet Union collapsed and especially after Vladimir Putin became the president of Russia, such cooperation between the state and the church intensified ever more. In the far abroad, the ROC helped the state to increase Russia’a influence in the Western world, while in the near abroad (in the post Soviet space), it played a role in reintegration of some of the ex-Soviet countries. However, especially after Russia’a annexation of Crimea, ie, after the Russian administration, instead of re-integration policy chose the policy of partition of Ukraine, implemenration of a “soft power” role became harder. Consequently, after the outbreak of the full scale invasion of Ukraine, ie, under the conditions of open invasion, the possibility to use the ROC as a soft power tool, decreased remarkably.

Ця стаття спробує аналізувати співробітництво між Російською державою та Російською Православною Церквою з минулого до сьогоднішнього дня. Як буде представлена в статті, в Росії держава завжди мала домінацію над церквою. Крім цього, Російська Православна Церква, за історію, складала ідеологічні стовпи Російської зовнішньої політики, такі як російське месіанство. Ця церква почала користуватися як м’яка сила, особливо під час Другої Світової Війни. З того часу, США були у співробітництво з Константинопольским Патріархатом тоді як Кремль підтримував Російську Православну Церкву. Після того як Радянський Союз розпався й особливо після того як Володимир Путин став президентом Росії, таке співробітництво стало ще інтенсивнішим. За кордоном РПЦ допомагає державі збільшити вплив у західному світі, у пострадянських країнах РПЦ сприяє політиці реінтеграції деяких колишніх радянських країн. Однак, особливо після анексії Криму Росією, тобто після того як російське керівництво замість політики реінтеграції обрало політику розчленування України, виконання ролі «м’якої сили» ускладнилось. В результаті, після початку повномасштабного вторгнення до України, можливість використання РПЦ як м’якої сили було зведено нанівець.
РОСІЙСЬКА ПРАВОСЛАВНА ЦЕРКВА – ІНСТРУМЕНТ ЗОВНІШНОЇ ПОЛІТИКИ РОСІЙСЬКОЇ ФЕДЕРАЦІЇ?
Keywords: Orthodoxy; the Russian Orthodox Church; Russian foreign policy; soft power; church – state relations; Russian World; War in Ukraine; Russia – Ukraine War; Orthodoxy; the Russian Orthodox Church; Russian foreign policy; soft power; church – state relations; Russian World; War in Ukraine; Russia – Ukraine War; Православ’я; Російська православна церква; м’яка сила; церковно-державні відносини; «руський мір»; російсько-українська війна; Православ’я; Російська православна церква; м’яка сила; церковно-державні відносини; «руський мір»; російсько-українська війна